Models and Software Model Checking of a Distributed File Replication System - Bjørner, Nikolaj (Springer-Verlag, 2007)
With the Distributed File System Replication component, DFS-R, as the central theme, we present selected protocol problems and validation methods encountered during design and development. DFS-R is currently deployed in various contexts; in Windows Server 2003-R2, Windows Live Messenger (Sharing Folders), and Windows Vista (Meeting spaces). The journey from an initial design sketch to a shipped product required mainly the dedicated effort of testers, developers, program managers, and several others; but in some places cute problems related to distributed consensus and software model-checking emerged. This paper presents a few of these, including a distributed garbage collection problem, distributed consensus problems for reconciling tree-like data structures, using model-based test case generation, and the use of software model checking in design and development process.